PHOTOBIOMODULATION ON MUSCLE STRENGTH AND FATIGUE IN MULTIPLE SCLEROSIS: SYSTEMATIC REVIEW - Santos, Heber; Santos, Yasmim; Ribeiro, Bianca; Artioli, Dérrick; Buzanello, Márcia; Bertolini, Gladson Ricardo Flor (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
Background: Photobiomodulation plays an important role in modulating the inflammatory process, accelerating tissue repair, which can be beneficial in cases such as multiple sclerosis. Objective: To carry out a literature review about effectiveness of photobiomodulation on muscle strength and fatigue in multiple sclerosis. Methods: The databases included were PubMed, Embase, Cochrane, Web of Science, Scopus and LILACS (Latin American and Caribbean Health Sciences Literature). Also the gray literature: Google Scholar, LIVIVO (ZB MED Search Portal for Life Sciences), Open Grey and Library of Thesis and Dissertations CAPES (Coordenação de Aperfeiçoamento de Pessoal de Nível Superior). The risk of bias was assessed using the Cochrane tool, Rob 2, and the data was extracted and assessed by blinded reviewers. Results: Initially 7302 records were found, 7102 in the main databases and 200 in the gray literature. After removing duplicates, 4217 studies were left for Phase 1 and 10 for Phase 2. Finally, 3 randomized clinical trials were included in this review. Conclusion: The studies included risk of bias in this review was predominantly low. PBM proved to be effective in improving muscle strength, but not fatigue. However, the number of human clinical trials is still too few for a more conclusive analysis.